Effect of anthraquinone on Buluh Madu soda pulping properties - Othman, Nor Hasyimah (2017)
The effect of anthraquinone on the Buluh Madu soda pulping properties was analysed. Bamboo chips were pulped in pulping digester with 14% active alkali at 170℃ cooking temperature for 90 minutes. In this study, the 0, 0.5 and 1.0% of AQ are added. The soda pulping shows the significant effect of all pulp to pulp yield. However, the ISO Standard hand sheet properties from Buluh Madu soda pulp not show a significant effect in the mechanical properties.